Sulfate anion templation of macrocycles, capsules, interpenetrated and interlocked structures. - Mullen, K; Beer, P (2009)
This tutorial review examines the potential of anions, in particular sulfate, to template the formation of complex molecular architectures. Until recently, sulfate has been largely overlooked in this area and the examples described herein demonstrate this anion's versatility in templating the formation of a diverse range of molecular systems including macrocycles, helixes, molecular capsules, interpenetrated and interlocked assemblies such as catenanes. In addition sulfate has been shown to template the formation of interpenetrated structures on a range of surfaces including gold, polystyrene beads and silicate nanoparticles, highlighting the potential of this anion in the fabrication of functional sensory devices exhibiting highly selective binding behaviour.